Artykuł oryginalnyThe effect of monosodium glutamate on rat thymocyte proliferation and Bcl-2/bax protein expression - Pavlović, Voja; Cekić, Snežana (Archives of Medical Science, 2006)
Introduction: Monosodium glutamate (MSG) is one of the commonest food additives in modern nutrition. Recent studies showed the modulatory effect of MSG on rat thymocyte apoptosis in vivo and under in vitro conditions. However, the influence of MSG on thymocyte proliferation is largely unknown. Material and methods: We evaluated the effect of increased MSG concentrations on thymocyte proliferation, as well as the expression of their two apoptosis-related proteins, Bcl-2 and Bax. Proliferation was detected by PCNA monoclonal antibody, and cells were analyzed using a flow cytometer. Expression of Bcl-2 and Bax protein were determined with flow cytometry, using respective monoclonal antibodies. Results: The results obtained in our study demonstrate that MSG significantly decreased thymocyte proliferation, in a dose dependent manner, followed by significantly increased cytotoxicity. The expression of Bcl-2 protein was significantly decreased, while Bax protein expression was not changed in our study. Conclusions: The results presented in our study indicate that MSG significantly modulated intensity of thymocyte proliferation as a consequence of increased cytotoxicity. The expression of Bcl-2 and Bax proteins suggests that this protein level is an important event in thymocyte cytotoxicity, triggered by MSG